Drought and recovery in barley: key gene networks and retrotransposon response - Paul, Maitry; Tanskanen, Jaakko; Jääskeläinen, Marko; Chang, Wei; Dalal, Ahan; Moshelion, Menachem; Schulman, Alan H. (Frontiers in Plant Science, 2023)
During drought, plants close their stomata at a critical soil water content (SWC), together with diverse physiological, developmental, and biochemical responses. Using precision-phenotyping lysimeters, we imposed pre-flowering drought on four barley varieties (Arvo, Golden Promise, Hankkija 673 and Morex) and followed their physiological responses. For Golden Promise, we carried out RNA-seq on leaf transcripts before and during drought, and during recovery, also examining retrotransposon BARE1 expression. Transcriptional data were subjected to network analysis. The varieties differed by their critical SWC, Hankkija 673 responding at the highest and Golden Promise at the lowest. Pathways connected to drought and salinity response were strongly upregulated during drought; pathways connected to growth and development were strongly downregulated. During recovery, growth and development pathways were upregulated; altogether 117 networked genes involved in ubiquitin-mediated autophagy were downregulated. The differential response to SWC suggests adaptation to distinct rainfall patterns. We identified several strongly differentially expressed genes not earlier associated with drought response in barley. BARE1 transcription is strongly transcriptionally upregulated by drought and downregulated during recovery unequally between the investigated cultivars. The downregulation of networked autophagy genes suggests a role for autophagy in drought response; its importance to resilience should be further investigated.